2′O-galloylhyperin attenuates LPS-induced acute lung injury via up-regulation antioxidation and inhibition of inflammatory responses in vivo. (1st May 2019) - Zhang, Sun-Dong; Wang, Peng; Zhang, Jing; Wang, Wei; Yao, Li-Ping; Gu, Cheng-Bo; Efferth, Thomas; Fu, Yu-Jie
Abstract: 2′ O -galloylhyperin, an active flavonol glycoside compound with remarkable anti-immune activity, was isolated from Pyrola [ P. incarnata Fisch.]. However, the evidence of anti-inflammatory activity in pulmonary diseases was still not convincing. The aim of the present study was (1) to investigate the effect of 2′ O -galloylhyperin on LPS-induced acute lung injury in mice, and (2) to identify the mechanisms of attenuation of inflammatory responses. The results demonstrated that 2′ O -galloylhyperin significantly reduced LPS-induced inflammation damage in a dose-dependent manner. After LPS challenge, treatment with 2′ O -galloylhyperin reduced the production of pro-inflammatory cytokines and chemokines, and also improved LPS-induced lung histopathology changes. 2′ O -galloylhyperin also increased the activities of antioxidant enzymes, including SOD and GSH-Px to maintain cellular redox homeostasis. Furthermore, 2′ O -galloylhyperin inhibited translocation of nuclear factor (NF-κB) activation and suppressed phosphorylation of MAPK signaling pathway consisting of p38, ERK, JNK. In addition, 2′ O -galloylhyperin enhanced heme oxygenase-1 (HO-1) expression to block LPS-induced inflammation via activating nuclear factor-crythroid 2-related factor (Nrf2). Moreover, 2′ O -galloylhyperin induced adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) phosphorylation. 2′ O -galloylhyperin attenuated LPS-induced acute lung injury by inhibiting the MAPK and NF-κB signaling pathways, presumably related to up-regulation of the AMPK and Nrf2 signaling pathways. Furthermore, 2′ O -galloylhyperin is a potential protective antioxidant to protect lung tissues from the acute injury. Highlights: 2′ O -galloylhyperin attenuated LPS-induced acute lung injury in vivo. 2′ O -galloylhyperin decreased the production of inflammation mediators. 2′ O -galloylhyperin suppressed the MAPK and NF-κB activation. 2′ O -galloylhyperin activated Nrf2 and AMPK signaling pathways.